ANALISIS PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, PROMOSI TERHADAP CITRA MEREK DAN MINAT BELI SERTA DAMPAKNYA PADA KEPUTUSAN PEMBELIAN KARTU PERDANA XL AXIATA DI SEMARANG - Wicaksono, Panji Usmar; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2017)
This study aimed to analyze the effect of product quality, price perception, and promotion of brand image and purchase interest and their impact on the purchase decision Axiata XL card in Semarang. Improving network quality in several areas including the farthest and improving the quality of the card so that no damage can enhance the brand image of XL Axiata, thus making consumers make purchasing decisions Axiata XL card. Perception prices and promotions have been done XL Axiata make consumers interested in buying, as well as increasing the purchasing decisions of consumers against Axiata XL card. Promotion XL Axiata very intensive to make the increase in purchase decisions Axiata XL card. XL Axiata brand image are important things to consider consumers to buy and increased the purchasing decisions of consumers against Axiata XL card.This study sampled using non-probability sampling technique, the respondents who have bought and used the card XL Axiata in Semarang. The collection of data obtained from 200 users Axiata XL card in Semarang by giving questionnaires. The analysis technique used in this research is Structural Equation Modeling (SEM) with Amos 22.The analysis showed that the product quality, price perception, and the campaign has a positive influence and significant impact on the brand image and purchase interest and their impact on the purchase decision Axiata XL card in Semarang.